The high Middle Ages : 1000-1300 (Sources in Western civilization ;, 1964)
The selections in this volume illustrate how Western European political and economic life revived so dramatically in the 11th century, and how that revival led to the rise of towns, to the growth of urban institutions and of the new bourgeoisie that transformed European society, and to the expansion of Western Europe epitomized by the Crusades and the economic movement that restored mastery of the Mediterranean to the West.